2018
DOI: 10.3901/jme.2018.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Coupled Vibration Mechanism of Bogie-body-seat System and Joint Optimization of Suspension Parameters for High-speed Train

Abstract: Abstract:For the problem of high speed train suspension parameters matching, using the method of system engineering, taking the bogie system, the car body, and the seat system as a unified whole system, a vertical dynamic model of high-speed train bogie-body-seat coupling system is established and the interaction between the systems is discussed. Based on this, taking optimal ride comfort as target, the optimization of the vertical suspension system of high-speed train under the excitation of track random irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…However, for complex practical engineering problems and special exploratory problems in the field of scientific research, it is quite difficult to apply multi-body dynamics software and finite element software in modeling, which brings many obstacles to the progress of work, and it is not easy to get effective dynamic analysis results; also, it is difficult to give innovative theories with guiding significance. In view of this, many researchers regarded the track support as a rigid fixed foundation, and established many passengertrain vertical coupling dynamic models by using the theory of system dynamics, [16][17][18] which brought great convenience to the practical vehicle engineering application.…”
Section: Specialmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for complex practical engineering problems and special exploratory problems in the field of scientific research, it is quite difficult to apply multi-body dynamics software and finite element software in modeling, which brings many obstacles to the progress of work, and it is not easy to get effective dynamic analysis results; also, it is difficult to give innovative theories with guiding significance. In view of this, many researchers regarded the track support as a rigid fixed foundation, and established many passengertrain vertical coupling dynamic models by using the theory of system dynamics, [16][17][18] which brought great convenience to the practical vehicle engineering application.…”
Section: Specialmentioning
confidence: 99%
“…Previous studies have shown that when evaluating the vertical random vibration characteristics of the human body in sitting posture, the human body subjected to whole body vibration can be simplified to a single-degree-of-freedom model. 18,19 Based on this, according to the actual structure of a railway vehicle, using the system engineering modeling method, regarding the human body as a single-degree-of-freedom system attached to the bottom of the carriage, taking the passenger, the train system, and the track system into a unified large system, a passenger-train-track vertical coupling dynamic model is established, as shown in Figure 1. Note that each row of the seat seated with five people in each carriage, NN rows in total.…”
Section: Passenger-train-track Vertical Coupling Dynamic Modelmentioning
confidence: 99%
“…At present, the main methods to solve the problems of bogie alarms and excessive lateral ride index caused by wheel hunting motion are wheel reprofiling and rail grinding, but this method is not economical. In addition, improper selection of damper parameters for vehicles IOP Publishing doi:10.1088/1742-6596/2760/1/012001 2 [9][10][11] or excessive track irregularity [12] can cause abnormal vibration of the car body and worsen the ride index.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of China's railway transportation, high-speed railways continue to rank first in the world in terms of mileage, and a large number of new railway passenger equipment put into operation. But in the process of high-speed railway operation, some hunting phenomena also appeared, including both the shaking car problem caused by primary hunting [1][2][3][4] and the bogie alarm caused by secondary hunting [5][6][7][8][9][10][11] . The main cause of the primary hunting is that the wheel-rail equivalent conicity is too low, which often occurs in the early stage of wheel reprofiling.…”
Section: Introductionmentioning
confidence: 99%